2004
DOI: 10.1074/jbc.m313062200
|View full text |Cite
|
Sign up to set email alerts
|

TOR Complex 1 Includes a Novel Component, Tco89p (YPL180w), and Cooperates with Ssd1p to Maintain Cellular Integrity in Saccharomyces cerevisiae

Abstract: The Tor1p and Tor2p kinases, targets of the therapeutically important antibiotic rapamycin, function as components of two distinct protein complexes in yeast, termed TOR complex 1 (TORC1) and TORC2. TORC1 is responsible for a wide range of rapamycin-sensitive cellular activities and contains, in addition to Tor1p or Tor2p, two highly conserved proteins, Lst8p and Kog1p. By identifying proteins that co-purify with Tor1p, Tor2p, Lst8p, and Kog1p, we have characterized a comprehensive set of protein-protein inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
292
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(315 citation statements)
references
References 55 publications
21
292
0
2
Order By: Relevance
“…Several components of the TORC1 and the Tap42-Sit4 complex localize to membranes of the protein secretory pathway (5)(6)(7)(8)(9)(10)(11)(12). Moreover, the EGO-GSE complex, which, in response to amino acids, controls sorting of the general amino acid permease Gap1, and, in combination with TORC1, regulates microautophagy, resides in prevacuolar compartments (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several components of the TORC1 and the Tap42-Sit4 complex localize to membranes of the protein secretory pathway (5)(6)(7)(8)(9)(10)(11)(12). Moreover, the EGO-GSE complex, which, in response to amino acids, controls sorting of the general amino acid permease Gap1, and, in combination with TORC1, regulates microautophagy, resides in prevacuolar compartments (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A prominent role for endogenous membranes of the protein secretory pathway as a platform for Tor signaling has begun to emerge: (i) different components of the Tor protein complexes, termed TORC1 and TORC2, as well as the Tap42-Sit4 phosphatase complex, have been localized to endosomal and vacuolar compartments (5)(6)(7)(8)(9)(10)(11)(12); (ii) a function for the Golgi Ca 2Ï© /Mn 2Ï© ATPase Pmr1 in negatively regulating TORC1 signaling has been demonstrated (13); and (iii) recent studies have shown genetic interactions between TORC1 and different components of the protein-sorting machinery, including those of the class C Vps complex that functions in docking and fusion of vesicles with the Golgi, endosomes, and vacuoles (refs. 9, 14, and reviewed in ref.…”
mentioning
confidence: 99%
“…Both Tor1 as well as Tor2 can be found in the multiprotein TORC1 together with Lst8, Kog1 and Tco89. A separate pool of Tor2 also associates with Lst8, Avo1, Avo2, Avo3, Bit61 and Bit2 to form TORC2 (Loewith et al 2002;Chen and Kaiser 2003;Wedaman et al 2003;Reinke et al 2004;Araki et al 2005;Fadri et al 2005). The precise function of these TORinteracting proteins is not known yet.…”
Section: The Tor Pathwaymentioning
confidence: 99%
“…First of all, ssd1 is highly pleiotropic. This locus has at least nine different names because of its having been identified in genetic screens for its effect on minichromosome stability, stress tolerance, membrane trafficking, and cell wall integrity, among other things Kosodo et al, 2001;Vannier et al, 2001;Reinke et al, 2004). Systematic global screens have identified Ïł200 genes that show genetic or physical interactions with Ssd1 (Reguly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%